Pemahaman Guru di Sekolah Katolik Terhadap Keragaman dan Inklusivitas: Studi Kasus di TK XYZ - Tita Rakhmita (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Pelita Harapan, 2022)
In recent years, Indonesia has faced increasing social conflicts related to diversity, some of which have also affected the education sector. Discrimination against children with HIV/AIDS, rejection of students with special needs, and religious-based restrictions highlight the urgent need for inclusive education. Early childhood education is expected to foster tolerance and respect for diversity from the very beginning, ensuring equal opportunities for all children as mandated by national law. his study employed a qualitative approach to explore teachers’ understanding and practices related to diversity and inclusive education in a Catholic-based kindergarten (TK XYZ) in East Jakarta. The findings indicate that teachers possess a generally positive understanding of inclusive education, emphasizing acceptance and accommodation of diverse student needs. TK XYZ demonstrates inclusive elements through a strong sense of belonging among staff and students, classroom practices encouraging collaboration, and a curriculum that introduces diversity from early themes. Hidden curriculum elements, collaboration with parents and external stakeholders, and supportive school policies further strengthen inclusivity. Challenges mainly arise from initial attitudes of students and parents, addressed by the school through discussions and modeling inclusive behavior. TK XYZ has effectively implemented inclusive education principles, integrating acceptance, collaboration, and policy support. However, continuous training, systematic parent engagement strategies, and reinforcement of inclusive practices remain essential for sustainability.